Kvantni algoritmi - Pompe, Miha (Matrika, 2022)
The aim of this paper is to examine how quantum computers and algorithms work, as well as to look into two models of computation: quantum gate array and adiabatic quantum computer. The models are used to solve two problems: Deutsch problem and financial portfolio optimization. The solutions for both problems are derived and it is shown how to implement them in a real quantum computer. Two quantum computer implementations are briefly discussed.
Keywords: adiabatic quantum computer; adiabatni kvantni računalnik; kvantna mehanika; kvantna vrata; kvantni računalniki; quantum computers; quantum gate array; quantum mechanics